1993
DOI: 10.1182/blood.v81.4.1009.1009
|View full text |Cite
|
Sign up to set email alerts
|

9-cis-retinoic acid: effects on normal and leukemic hematopoiesis in vitro

Abstract: Retinoic acid exhibits effects on the proliferation and differentiation of many hematopoietic cells. Cellular responsiveness to retinoic acid (RA) is conferred through two distinct classes of nuclear receptors, the RA receptors (RARs) and the retinoid X receptors (RXRs). The RARs bind to both 9-cis- and all-trans-RAs, but 9-cis-RA alone directly binds and activates RXR. This suggested that 9-cis-RA could have expanded hematopoietic activities as compared with all-trans-RA. We compared the abilities of 9-cis- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…9cRA (100 nM) increased NBT-reducing activity in THP-1 and HL60 cells, while ATRA (100 nM) was not effective ( Fig. 1A ), consistent with the previous reports showing that 9cRA is more potent than ATRA in inducing differentiation of leukemia cells [20] , [31] , [32] . In combination with 1,25(OH) 2 D 3 , 9cRA and ATRA effectively increased NBT-reducing activity in these cells ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…9cRA (100 nM) increased NBT-reducing activity in THP-1 and HL60 cells, while ATRA (100 nM) was not effective ( Fig. 1A ), consistent with the previous reports showing that 9cRA is more potent than ATRA in inducing differentiation of leukemia cells [20] , [31] , [32] . In combination with 1,25(OH) 2 D 3 , 9cRA and ATRA effectively increased NBT-reducing activity in these cells ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…9cRA exhibits differentiation-inducing activity more effectively than ATRA in the absence or presence of 1,25(OH) 2 D 3 ( Figs. 1 and 2 ), in agreement with previous reports [20] , [31] , [32] . Since 9cRA acts as a ligand for both RAR and RXR [40] , synergistic activation may be due to binding to both RAR and RXR in the RAR−RXR heterodimer.…”
Section: Discussionsupporting
confidence: 93%
“…Retinoids have critical functions in many aspects of human biology: at the cellular level, they control cell differentiation, growth, and apoptosis [ 3 ]. Several biologically active vitamin A derivatives, namely, all- trans retinoic acid (ATRA), 9- cis retinoic acid (9- cis- RA), and 13- cis retinoic acid (13- cis -RA), have been tested for potential use in cancer therapy and chemoprevention [ 4 7 ]. The most effective clinical use of ATRA was demonstrated in acute promyelocytic leukemia (APL) treatment [ 8 ].…”
Section: Natural and Synthetic Retinoids In Anticancer Treatmentmentioning
confidence: 99%
“…Several studies have explored the efficiency of ATRA and liposomal ATRA in combination with chemotherapy to induce differentiation and apoptosis or to reduce clonogenic capacity in non-APL AML cell lines [86,87] and primary AML patient cells [88][89][90]. Moreover, some clinical trials showed the effectiveness of ATRA in combination with chemotherapy for AML patients [91,92], whereas others had disappointing results [93][94][95][96].…”
Section: Ra Therapy In Aplmentioning
confidence: 99%